Pengaruh Model Pembelajaran NHT (Numbered Head Together) Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 091524 PNP Tonduhan - Ica Maysari Siallagan; Canni Lorent Sianturi; Jumaria Sirait (Departement of Mathematics Education, 2023)
This study aims to determine whether the use of interactive Powerpoint Media has an effect on the learning outcomes of fifth grade students at SD Negeri 095198 Silomaria in learning 6 Sub-theme 2 Humans and the Environment or has no effect. There are 2 hypotheses in this study, namely, (1) there is an effect of the use of interactive PowerPoint learning media on the learning outcomes of fifth grade students at SD Negeri 095198 silomaria (H1) and there is no effect of using interactive PowerPoint media on learning outcomes for fifth grade students at SD Negeri 095198 Silomaria ( H0). This research method is an experimental method with the type of Pre-Experimental Design research that uses the One Group Pretest-posttest Design. The population of this study were all fifth grade students at SD Negeri 095198 Silomaria, which consisted of 21 students. Because the population is less than 50, the population is less than 50 students, so the population is used as the sample in this study. Data collection was carried out by giving tests and observation techniques. The research data were analyzed using descriptive and inferential statistical analysis. Based on the results of data analysis it is known that the result of t count is 7.18 with a significance level of 0.05. So it can be concluded that there is an effect of using Interactive Powerpoint Media on Learning Outcomes of Class V Students of SD Negeri 095198 Silomaria Tanah Jawa subtheme 2 Humans and the Environment. This means that H1 is accepted and H0 is rejected.